RELIGION AS AN EFFECTIVE INSTRUMENT IN PRISONER RESOCIALIZATION (REMUNOM, 2024)
The objective of the present work is to analyze the influence that religion has on the process of resocialization of the prisoner serving a sentence for committing crimes. For this, we bring up the Federal Law 7.210/84, the Federal Constitution, in addition to other provisions of the legal system that ensure religious assistance to the incarcerated. The research sought to demonstrate the benefits that religion brings to prisoners in these environments, as well as its importance in resocialization, and also brought some data on the result obtained after religion was used for resocialization in the prison environment.